2019
DOI: 10.1002/adfm.201905054
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Self‐Assembly of Nanoconfined Ionic Liquids for Fast Anisotropic Ion Transport

Abstract: Materials involving nanoconfinement of ionic liquids (ILs) have been pursued for functionalities and ionic devices. However, their complex synthesis, challenges to achieve long-range order, and laborious tunability limit their practical implementation. Herein, these challenges are addressed by complexing surfactants to ILs, yielding a facile, modular, and scalable approach. Based on structural screening, ionic complexation of di-n-nonylamine to the terminal sulfonic acid of 1-(4-sulfobutyl)-3-methylimidazolium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Even though cubic phases tend to promote particularly high conductivities due to the 3D interconnectivity, lamellar LC phases promoted by rod-like molecules can also assist conductivity by reducing ionic aggregation in electrolytes [86][87][88]. Cherian et al [89] have very recently reported parallel conductivities of 10 - hydrogen sulfate. These values are like those shown here, and are superior to some state-of-theart polymerized ionic liquid electrolytes [90], and comparable to phosphonium or imidazoliumbased ionic liquids (10 -2 S cm -1 , at 30 o C) and to dicationic imidazolium salts forming SmA phases (10 -6 to 10 -4 S cm -1 , near room temperature) [91][92][93].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Even though cubic phases tend to promote particularly high conductivities due to the 3D interconnectivity, lamellar LC phases promoted by rod-like molecules can also assist conductivity by reducing ionic aggregation in electrolytes [86][87][88]. Cherian et al [89] have very recently reported parallel conductivities of 10 - hydrogen sulfate. These values are like those shown here, and are superior to some state-of-theart polymerized ionic liquid electrolytes [90], and comparable to phosphonium or imidazoliumbased ionic liquids (10 -2 S cm -1 , at 30 o C) and to dicationic imidazolium salts forming SmA phases (10 -6 to 10 -4 S cm -1 , near room temperature) [91][92][93].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…ILs that form the continuous phase of INFs have several advantages: wide liquid range, high chemical and thermal stabilities, and very low vapor pressure. Especially important is that ILs have optimal thermophysical properties as a base fluid for heat transfer systems, studied in detail by França et al, Tenney et al, Chernikova et al, and our group. , Moreover, a great diversity of results from a number of possible anion–cation combinations for ILs makes it possible to design a structure with optimal properties, allowing many functionalities for very specific purposes . Thus, the use of ILs as a continuous phase of nanodispersions means that the INFs can be designed to meet any specific application or task requirement .…”
Section: Introductionmentioning
confidence: 95%
“… 8 , 9 Moreover, a great diversity of results from a number of possible anion–cation combinations for ILs 10 makes it possible to design a structure with optimal properties, allowing many functionalities for very specific purposes. 11 Thus, the use of ILs as a continuous phase of nanodispersions means that the INFs can be designed to meet any specific application or task requirement. 12 Cyano alkylimidazolium ILs such as [EMIM][SCN] seem to be particularly useful because of their low viscosity and acceptable ecotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 148 ] Layered ionic liquids with nanoconfined nanochannels were constructed through complexation between surfactants and ionic liquids, showing temperature‐mediated ion transport along the parallel and normal directions. [ 149 ] Recently, 2D nanochannel‐structured membranes with special surface and nanochannel arrangement structures have attracted the attention of researchers. For instance, anti‐T [ 39 ] MXenes showed ion transport in the vertical direction because of the specific surface structure and vertically aligned [ 40 ] structure, exhibiting rapid ion transport owing to the efficient ion transport pathways resulting from the arrangement structure.…”
Section: Nanochannel‐structured Membranesmentioning
confidence: 99%